2010
DOI: 10.1038/hr.2010.211
|View full text |Cite
|
Sign up to set email alerts
|

Plasma heparin cofactor II activity is inversely associated with left atrial volume and diastolic dysfunction in humans with cardiovascular risk factors

Abstract: Thrombin has a crucial role in cardiac remodeling through protease-activated receptor-1 activation in cardiac fibroblasts and cardiomyocytes. As heparin cofactor II (HCII) inhibits the action of tissue thrombin in the cardiovascular system, it is possible that HCII counteracts the development of cardiac remodeling. We investigated the relationships between plasma HCII activity and surrogate markers of cardiac geometry, including left atrial volume index (LAVI), relative wall thickness (RWT) and left ventricula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In experimental animal studies, we and Vicente et al revealed that HCII-deficient mice showed more prominent intimal hyperplasia after vascular injury than did in wild-type (WT) littermates (11,12). In addition, plasma HCII activity is inversely associated with acceleration of human and murine cardiac remodeling including atrial enlargement and left ventricular concentric alteration (13,14). These findings revealed that HCII plays a protective role in the development of vascular remodeling and cardiac remodeling in humans and mice.…”
Section: Heparin Cofactor II (Hcii)mentioning
confidence: 71%
See 1 more Smart Citation
“…In experimental animal studies, we and Vicente et al revealed that HCII-deficient mice showed more prominent intimal hyperplasia after vascular injury than did in wild-type (WT) littermates (11,12). In addition, plasma HCII activity is inversely associated with acceleration of human and murine cardiac remodeling including atrial enlargement and left ventricular concentric alteration (13,14). These findings revealed that HCII plays a protective role in the development of vascular remodeling and cardiac remodeling in humans and mice.…”
Section: Heparin Cofactor II (Hcii)mentioning
confidence: 71%
“…We have shown pathophysiological roles of HCII action such as protective effects against cardiovascular remodeling (8,9,(12)(13)(14)16). In addition, Huang et al showed that plasma HCII activity is positively correlated with flow-mediated vasodilatation, a marker of endothelial function, suggesting that HCII increases NO bioavailability in humans (40).…”
Section: Patients and Animals With Peripheral Circulation Insufficienmentioning
confidence: 99%
“…The thrombin-PAR system promotes CVDs and insulin resistance, and HCII is an endogenous mammalian thrombin inhibitor; therefore, we hypothesized that HCII prevents CVDs and preserves insulin sensitivity. Indeed, we previously reported that low plasma HCII activity was associated with the development of atherosclerosis, cardiac remodeling, and hyperglycemia with insulin resistance in humans 13,14,16,18,21 . Moreover, we generated heterozygous HCII-deficient mice by a gene-targeting method and demonstrated that the HCII-deficient mice manifested exaggerated cardiovascular remodeling and enhanced insulin resistance with increased gluconeogenesis 15,[19][20][21] .…”
Section: Hcii Prevents Cvds and Insulin Resistance Via Inactivation Of The Thrombin-par-1 Systemmentioning
confidence: 98%
“…HCII is synthesized by hepatocytes and secreted into the bloodstream at a concentration of approximately 1.0 lmol/ L, and upon activation by binding to dermatan sulfate proteoglycans, it specifically inhibits thrombin activities in various tissue matrices 12 . We and others have shown that HCII prevents the development of cardiovascular diseases (CVDs) [13][14][15][16][17][18][19][20] and ameliorates insulin resistance 21 by attenuating thrombinmediated PAR activation.…”
Section: Introductionmentioning
confidence: 99%
“…We generated heterozygous HCII-deficient mice and demonstrated that the mutant mice manifested exaggerated cardiovascular remodeling 22,[36][37][38] and enhanced insulin resistance with increased gluconeogenesis 26) . In addition, we previously found that cuff injury and HFD feeding prominently augmented MCP-1 gene expression in arterial walls and in epidydimal fat of heterozygous HCII-deficient mice, respectively 22,26) .…”
Section: Limitationsmentioning
confidence: 99%